Examining the effects of the Contract Based Supply Chain Management in Cyprus Turkish Construction Industry - Dannoun, Yazan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Over the last few decades, development part of Turkey has been growing rapidly, Economically Turkish government has assigned a noteworthy accentuation over the industry as a subsequent of the heightening public request of business, mechanical and private developments including low-cost residential construction. For that reason, a well-disciplined remedy intending to minimize waste, time and cost in construction industry to confront the situation looks to be vital. It is controverted that one of the dependable practices that predominantly might be the remedy to construction industry’s dispute, time and cost excess is the Supply Chain Management (SCM), the concept that has firstly appeared and progressed in car manufacturing industry where has attained success to manufacturing business. Construction industry has the faith that Supply Chain Management has high possibility in enhancing the productivity of implementing the activities of construction process. However, this practice has not been adequately applied in many countries especially in Northern Cyprus and Turkey. The main aim of this study is asses and examine the SCM implementation process in Cyprus Turkish construction industry with focus on the effective procurement and supply of building materials with the implementation of a valid written contract. This, it is planned to achieve by differentiating the weaknesses and strengths of this industry by a detailed literature review, then checking up the existing act of the industry all the way through a questionnaire survey gathered from construction industries’ stakeholders and experts. The model framework of our study will include the benefits of contracts in the application of SCM in the construction industry; barriers (lack of a well written contract) of the effective implementation SCM in the procurement and delivery of building materials, and factors that strengthen the implementation. Keywords: Contract, Cyprus Turkish Construction Industry, Framework Model, Procurement, Supply Chain Management.

ÖZ: Son birkaç yıl içinde, Türkiye 'nin Kalkınma Bölümü hızla büyüyor, ekonomik Türk hükümeti, iş, mekanik ve özel en yüksek sosyal istek bir sonraki olarak bu sektörde önemli bir vurgulu atandı gelişmeler özellikle düşük maliyetli konut ve uygun fiyatlı konaklama. Bu nedenle, inşaat sektöründeki maliyet, zaman ve atıkların azaltılması amacıyla iyi organize edilen bir dönüşüm bu durumla başa çıkmak için gerekli görünüyor. Bu muhtemelen inşaat endüstrisinin çatışmalar ve zaman ve maliyet taşmaları için çözüm olabilir iyi düşünce teknikleri biri tedarik zinciri yönetimi (SCM), ortaya çıktı ve araba imalat sektöründe geliştirilen kavramı olduğunu savunuyor ve bu sektöre de başarı getirdi. Bu tedarik zinciri yönetimi birçok yönden inşaat endüstrisinin genel verimliliğini artırmak için potansiyele sahip olduğuna inanılmaktadır. Ancak bu teknik özellikle Türkiye 'de pek çok ülkede verimli bir şekilde uygulanmamıştır. Bu çalışmanın ana amacı, Türk inşaat sektöründe SCM uygulama amacı ile geçerli bir yazılı bir uygulama ile yapı malzemelerinin etkili alımı ve temini üzerine odaklanarak yeterli bir kavramsal çerçeve geliştirmektir Sözleşme. Bu, ayrıntılı bir literatür incelemesi yoluyla bu sektörün güçlü ve zayıf noktalarını ayırt ederek, endüstrinin uzmanlarından toplanan bir anket anketi boyunca sektörün mevcut performansını analiz ederek elde etmek planlanmaktadır. Paydaş -ların. Çalışmamızda model çerçevesi, SCM 'nin inşaat sektöründe uygulanmasında sözleşmelerin avantajlarını içerecek; engelleri (iyi yazılı bir sözleşme eksikliği) etkili uygulama SCM tedarik ve yapı malzemelerinin teslim ve uygulama güçlendirmek faktörler. Anahtar kelimeler: Türk inşaat endüstrisi, Tedarik Zinciri Yönetimi, Tedarik, Sözleşme.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Co-Supervisor: Assoc. Prof. Dr. İbrahim Yitmen and Supervisor: Assoc. Prof. Dr. Tolga Çelik.
Keywords: Civil Engineering; Construction Industry--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; Business logistics--Data processing--Construction; Materials Management; Engineering contracts; Contract; Cyprus Turkish Construction Industry; Framework Model; Procurement; Supply Chain Management